TINJAUAN YURIDIS TENTANG HAK ATAS TANAH PERUSAHAAN DI KAWASAN INDUSTRI DI INDONESIA - Ilhamdi Ilhamdi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Management of industrial areas often face obstacles, such as: setting the industrial area and the implementation of the transfer of land in an industrial area, so that in the process of implementation of the transfer of land in the industrial park needs to be disseminated land use plan with the community or the land owner, the measurement of land area to be released, a detailed mapping of parcels of land to be entered into the industrial area plan, land selling price agreements with landowners, paying the price of land, the people affected by land acquisition or affected have priority to go to work or effort. Moreover, to overcome obstacles in managing the industry, is the need for state intervention as the manifestation of the sovereignty of the state in the economy. Intervention is meant by the author not only through the release of products of the general law, but a special legal product which thoroughly so there is legal certainty and legal synchronization in economic management in industrial areas, like made law on industrial estates.